Dead Today, Gone Tomorrow: The Framing of Workplace Injury in Canadian Newspapers, 2009-2014. - Foster, Jason; Barnetson, Bob (Canadian Journal of Communication, 2017)
Background: How the media frames and presents a subject influences how society sees and responds to that issue. Analysis: This study uses frame analysis to examine how Canadian English language newspapers portrayed workplace injuries between 2009 and 2014. Three frames emerge: Under Investigation, Human Tragedy, and Before the Courts. There is also a meta-frame casting injuries and fatalities as isolated events happening to “others” with no cause, thus the public ought not be concerned about workplace safety. Conclusion and implications: The article concludes that media frames obscure issues of cause and fault, thereby denying workers a full understanding of why injuries happen in the workplace. These frames serve the interests of employers by obfuscating the employer’s role in creating workplace injury and death.